ANALISIS PERSEPSI MASYARAKAT DALAM MENGGUNAKAN PRODUK BANK SYARIAH - Irma Damayanti; Ahsan Putra Hafiz; Refky Fielnanda (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2023)
The purpose of this study was to determine how the perception of the people of Kampung Baru, Kec. Muara Tembesi about Islamic banks. The author uses qualitative methods by using data collection methods by means of interviews, observations, documentation and drawing conclusions. The results of this study found that the perceptions of the people of Kampung Baru were different. There are four categories that are perceived by the public, namely Islamic banks that have operated using sharia principles, which are 67%, Islamic banks which are considered not yet fully operating using sharia principles, which are 15%, Islamic banks as a forum if there is a need, which is 11%, really. really do not understand Islamic banks by 24%. And there are four factors that influence the four categories, namely personal factors, psychological factors, and social factors